The Effectiveness of Health Education Learning Module Based on WebQuest Among Special Education Instructors - Alijah Ujang; Norlidah Alias; Khairul Azhar Jamaludin; Syed Ismail Syed Noh (Department of Special Education, 2018)
The WQPKes Module for Special Education Instructors is a learning platform with WebQuest, in helping to increase the instructors’ learning experiences in Health Education. In measuring its effectiveness, this module was implemented and tested in the PDK in Gombak, Malaysia. Under the Department of Social Welfare, Malaysia PDK is established in a community to help people with disabilities (PWDs) in providing early interventions and rehabilitation services. This study focussed on food and nutrition topic in WQPKes module. This study employed an exploratory implementation design which incorporated a quasi-experimental research design. The findings showed that the instructors’ knowledge on all elements in food and nutrition has improved after the implementation of this module. Potentially, this module could be implemented in other PDKs in Malaysia.